School teachers' awareness of internet addiction in elementary school students: a regional survey in Japan - Kawabe, Kentaro; Horiuchi, Fumie; Hosokawa, Rie; Nakachi, Kiwamu; Soga, Junya; Ueno, Shu-ichi (Frontiers in Psychiatry, 2023)
In recent years, concerns about Internet addiction (IA) among children have been increasing. The present study focused on the awareness of IA in elementary school teachers. A web-based anonymous survey was conducted in November 2021. The participants completed an original questionnaire about their awareness of IA. The participants were divided into three groups based on their positions in the classroom: class teachers, support teachers, and administrative teachers. Out of 283 participants, over 70% had not approached students with IA and had little practical knowledge about the disorder. Support and administrative teachers had more opportunities to interact with students with IA than class teachers (p<0.001 in both cases). Support teachers had more opportunities to ask their colleagues about IA than class teachers (p<0.01); similarly, administrative teachers also had more opportunities to discuss IA with colloeagues than class teachers (p=0.04). Preventive interventions are recommended for people who communicate with children with IA. Students with IA might cause anxiety among teachers; therefore, preventive education strategies should be implemented with the cooperation of psychiatrists, psychologists, and public health nurses.